Hiba hiba hátán: Szállóige és protestáns műbíráló epigramma Csokonai Vitéz tollából - Rédey-Keresztény, János (Studia Litteraria, 2024)
A composite volume in the Hungarian National Library contains a signature by Csokonai Vitéz Mihály (1773–1805). However, instead of Csokonai V. Mihály, the signature uses an unusual form, “Cs. V.”, meaning that Vitéz (roughly meaning ‘virtue’) functions as a proper name. The handwritten note also contains a two-line Hungarian epigram, unanimously attributed to Csokonai as a book review in the milieu of the Reformed colleges in the Kingdom of Hungary. This paper presents arguments, based on Csokonai’s sentimental poetry, suggesting — without absolute certainty — that the signature is more likely than not to be that of Csokonai’s. The paper also examines the European context of the epigram, concluding that the verse is a translation, the original of which was written in Latin during a critical period of the European Protestantism (1570–1580).